EKOLEKSIKON DALAM KUMPULAN LAGU DAERAH SUKU KUTAI, KALIMANTAN TIMUR: KAJIAN EKOLINGUISTIK - Rahman, Abdur; Yudista, Rensiana; Barack, Choirunnisa Fadilla; Wahyuni, Ian (Diterbitkan oleh Jurusan Sastra Indonesia Fakultas Ilmu Budaya Universitas Jember bekerja sama dengan Himpunan Sarjana - Kesusastraan Indonesia (HISKI), Himpunan Pembina Bahasa Indonesia (HPBI) dan Masyarakat Linguistik Indonesia (MLI), 2024)
This research aims to discuss the language styles and natural lexicon found in the lyrics of Kalimantan regional songs, especially Kutai. This research is a type of library research with an ecolinguistic approach. The method used is a qualitative method with descriptive analysis. The material objects are the lyrics of regional songs from the Kutai tribe, East Kalimantan, namely the lyrics of the songs